2016
DOI: 10.1002/adsc.201501103
|View full text |Cite
|
Sign up to set email alerts
|

Transition Metal‐Free Approach to Propynenitriles and 3‐Chloropropenenitriles

Abstract: At ransitionm etal-free,f acile and efficient one-pot protocol for the synthesiso fp ropynenitriles from readilya vailable 3-chloropropenals is disclosed. Ther eactionc onditions have also been optimized for the exclusive formation and isolation of 3-chloropropenenitriles which are important building blocks in general anda re intermediates in the synthesis of propynenitriles.T he hallmark of the methodology is the use of non-toxic reagents, milder, metal-free ande conomically benign reaction conditions avoidin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…6 and 8 for conditions). Instead, it was found that the desired product could easily be obtained from a Diels-Alder reaction between the known 27 para and meta bis(cyanoethynyl)benzenes 12 and 13 , respectively, with cyclopentadiene (under microwave heating) affording the dimers 14 and 15 in yields of 77 and 45%.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6 and 8 for conditions). Instead, it was found that the desired product could easily be obtained from a Diels-Alder reaction between the known 27 para and meta bis(cyanoethynyl)benzenes 12 and 13 , respectively, with cyclopentadiene (under microwave heating) affording the dimers 14 and 15 in yields of 77 and 45%.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Elemental analyses were performed at London Metropolitan University. Compounds 3 14 , 12 27 , and 13 27 were made by their respective literature methods.…”
Section: Methodsmentioning
confidence: 99%
“…Two approaches were employed in the synthesis of NBD derivatives (full experimental procedures can be found in the Supporting Information), one involving a [4+2π] Diels–Alder route, in which by using a literature method, suitable dienophiles could be made on a large scale from a host of acetophenones furnishing the set of NBDs shown in Figure . In the cases where the initial method did not work, this was supplemented by the reported procedure employing a palladium‐catalysed Suzuki reaction upon 2‐chloro‐3‐cyanonorbornadiene .…”
Section: Figurementioning
confidence: 99%
“…Twoa pproaches were employedi nt he synthesiso fN BD derivatives (full experimental procedures can be found in the Supporting Information), one involvinga[ 4 + 2p]D iels-Alder route, in which by using al iterature method, suitable dienophiles could be made on al arge scale from ah ost of acetophenones furnishing the set of NBDs shown in Figure 3. [9] In the cases where the initial methodd id not work, this was supplemented by the reported procedure employing ap alladiumcatalysed Suzuki reaction upon 2-chloro-3-cyanonorbornadiene. [7g] Ar ecent theoretical study showed that certain aromatic donoru nits could enhance the MOST properties,i ncluding dimethylaniline andt hiophene, among other electron rich substituents, which werea ccordingly included in this series.…”
mentioning
confidence: 99%
“…A more general, transition metal-free approach to 2-alkynylnitriles from 3-chloropropenals (11) was disclosed by Sharma et al in 2016 employing non-toxic reagents and mild aqueous reaction conditions (Scheme 10). [27] In the same year, Skrydstrup and co-workers found that 2alkynylnitriles could be obtained from the corresponding βketonitriles upon treatment with triethylamine in combination with Mukaiyama's reagent (2-chloro-1-methylpyridinium iodide) followed by the addition of aqueous sodium hydroxide in 72 % yield. [28] In addition, Shu et al developed an efficient metal-free protocol towards 2-alkynylnitriles by the treatment of 3-oxo-3phenylpropionitrile with LiHMDS-ClPO(OEt) 2 at À 78°C.…”
Section: Synthesis Of 2-alkynylnitrilesmentioning
confidence: 99%